2016
DOI: 10.1002/14651858.cd010675.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interventions (microfracture, drilling, mosaicplasty, and allograft transplantation) for treating isolated cartilage defects of the knee in adults

Abstract: Surgical interventions (microfracture, drilling, mosaicplasty, and allograft transplantation) for treating isolated cartilage defects of the knee in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 64 publications
0
59
0
2
Order By: Relevance
“…PoC in the rabbit model allowed evaluation of the cartilage repair potential of the GGMA 2% w/V hydrogel as compared with MFX treatment. Currently considered as a gold‐standard treatment, MFX still has limitations on what concerns the quality of the regenerated tissue, which can ultimately lead to treatment failure upon recurrence of symptoms . In this study, MFX group outcome showed formation of a thin layer of chondral tissue concurrent with subchondral bone overgrowth and an irregular surface.…”
Section: Discussionmentioning
confidence: 80%
“…PoC in the rabbit model allowed evaluation of the cartilage repair potential of the GGMA 2% w/V hydrogel as compared with MFX treatment. Currently considered as a gold‐standard treatment, MFX still has limitations on what concerns the quality of the regenerated tissue, which can ultimately lead to treatment failure upon recurrence of symptoms . In this study, MFX group outcome showed formation of a thin layer of chondral tissue concurrent with subchondral bone overgrowth and an irregular surface.…”
Section: Discussionmentioning
confidence: 80%
“…Скептические результаты этого метаанализа поддер-живает и более поздняя работа Кохрановского общества, опубликованная в 2016 г. Оценив данные серии исследова-ний, в которых изучались разные методы микрохирургиче-ского лечения ОА, авторы пришли к выводу о недостаточ-ном уровне доказательств эффективности АТХ [83].…”
Section: ау тологичная трансплантация хондроцитовunclassified
“…The former employ techniques that stimulate tissue cells to form hyaline cartilage, such as the microfracture technique, perforation, abrasion arthroplasty, and biological procedures involving cell culture, such as autologous chondrocyte implantation (ACI), of the later derives the development of biocompatible three-dimensional scafolds, where chondrocytes, stem cells, or chondrocyte-like cells can be grown. The later involves mosaicplasty, such as the transplantation of autografts or allografts, which are composed of mature hyaline cartilage atached to the subchondral bone [128]. The type of treatment to be used will depend on the size of the lesion, the location, and the type of activity of the patient.…”
Section: The Eicacy and Safety Of Diferent Treatments Of Cartilage Inmentioning
confidence: 99%